Analisis Penerapan Metode Gross Up PPh Pasal 21 sesuai PSAK 46 untuk meminimalkan Pajak Penghasilan Badan (Studi Kasus pada PT. XYZ) - Anisa Fitria Islamy; Deasy Ervina (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2021)
Since Law Number 36 of 2008 regultes General Provisions and Taxprayers in payin mandatory contributions to the government as well as receiving all forms of convenience to taxprayers in the tax process. The purpose of this research is to find out the calculation of Article 21 Gross Up Method Income Tax according to PSAK 46 can Minimize Corporate Income Tax at PT. Treston.As for the type of research used is qualitative reaserch where researchers look for employee salary document at PT. Treston to calculate of Article 21 Income Tax allowance using the Gross Up Method.The conclusion of this study is the Gross Up Method proposed by researchers can facilitate the company in finding tax benefits for permanent employee at PT. XYZ.